Targeting the TGFβ pathway with galunisertib, a TGFβRI small molecule inhibitor, promotes anti-tumor immunity leading to durable, complete responses, as monotherapy and in combination with checkpoint blockade. Issue 1 (4th June 2018) - Holmgaard, Rikke B.; Schaer, David A.; Li, Yanxia; Castaneda, Stephen P.; Murphy, Mary Y.; Xu, Xiaohong; Inigo, Ivan; Dobkin, Julie; Manro, Jason R.; Iversen, Philip W.; Surguladze, David; Hall, Gerald E.; et al.
Abstract : Background: TGFβ signaling plays a pleotropic role in tumor biology, promoting tumor proliferation, invasion and metastasis, and escape from immune surveillance. Inhibiting TGFβ's immune suppressive effects has become of particular interest as a way to increase the benefit of cancer immunotherapy. Here we utilized preclinical models to explore the impact of the clinical stage TGFβ pathway inhibitor, galunisertib, on anti-tumor immunity at clinically relevant doses. Results: In vitro treatment with galunisertib reversed TGFβ and regulatory T cell mediated suppression of human T cell proliferation. In vivo treatment of mice with established 4T1-LP tumors resulted in strong dose-dependent anti-tumor activity with close to 100% inhibition of tumor growth and complete regressions upon cessation of treatment in 50% of animals. This effect was CD8+ T cell dependent, and led to increased T cell numbers in treated tumors. Mice with durable regressions rejected tumor rechallenge, demonstrating the establishment of immunological memory. Consequently, mice that rejected immunogenic 4T1-LP tumors were able to resist rechallenge with poorly immunogenic 4 T1 parental cells, suggesting the development of a secondary immune response via antigen spreading as a consequence of effective tumor targeting. Combination of galunisertib with PD-L1 blockade resulted in improved tumor growth inhibition and complete regressions in colon carcinoma models, demonstrating the potential synergy when cotargeting TGFβ and PD-1/PD-L1 pathways. Combination therapy was associated with enhanced anti-tumor immune related gene expression profile that was accelerated compared to anti-PD-L1 monotherapy. Conclusions: Together these data highlight the ability of galunisertib to modulate T cell immunity and the therapeutic potential of combining galunisertib with current PD-1/L1 immunotherapy.